2014
DOI: 10.11613/bm.2014.026
|View full text |Cite
|
Sign up to set email alerts
|

Recreational scuba diving: negative or positive effects of oxidative and cardiovascular stress?

Abstract: Environmental conditions and increased physical activity during scuba diving are followed by increased production of free radicals and disturbed redox balance. Redox balance disorder is associated with damage of cellular components, changes of cellular signaling pathways and alterations of gene expression. Oxidative stress leads to increased expression of sirtuins (SIRTs), molecules which play an important role in the antioxidant defense, due to their sensitivity to the changes in the redox status and their ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 74 publications
2
25
0
1
Order By: Relevance
“…This may be due to the fact that they are too small to be detected owing to the insufficiently high imaging resolution of ultrasonic equipment. The long-term consequences of these -asymptomatic -decompression-induced inflammatory phenomena are not clear [10].…”
Section: Prevention Of Decompression Sicknessmentioning
confidence: 99%
“…This may be due to the fact that they are too small to be detected owing to the insufficiently high imaging resolution of ultrasonic equipment. The long-term consequences of these -asymptomatic -decompression-induced inflammatory phenomena are not clear [10].…”
Section: Prevention Of Decompression Sicknessmentioning
confidence: 99%
“…Contrary to the technical scuba diving, performed by professional divers at demanding depths using different gas mixtures, recreational or sports scuba diving implies diving to a depth of not more than 40 m, using only compressed air or nitrox (mixture of nitrogen and oxygen with no more than 40% oxygen), and never requiring a mandatory decompression stop [1]. In any case, scuba diving represents a special form of exercise-induced oxidative stress since the increased production of reactive oxygen species (ROS) is a result not only of a demanding physical activity but also of the exposure to low temperature and hyperoxia, which occurs due to exposure to the elevated pressure and breathing oxygen under increased pressure [2]. High production of ROS causes oxidative damage of the cellular structures such as lipids, proteins, and nucleic acids, and the accumulation of these damages can result in relevant changes in health status [3].…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing studies suggest that diving is associated with changes in oxidative stress and the increased expression of regulatory proteins [13] the consequences of which are unclear. Changes in CV function after recreational or professional diving have been observed in many studies but it has frequently been concluded that confounding factors, such as physical activity or temperature, are the cause of any changes detected [14, 15].…”
Section: Introductionmentioning
confidence: 99%